Building digital collections in a public university library in Ghana: priority‐setting and user needs assessment. Issue 2 (2014) - Nesba Yaa Anima Adzobu
<x xml:space="preserve"> Abstract </x> Purpose – Although user needs assessment is an intrinsic element of service quality delivery in digital libraries (DLs), not much has been written on this topic in the context of African universities. This is understandable as academic digital libraries in Africa are rather nascent. Even so, the most frequently‐used needs assessment methods do not directly involve the users. This study aims to assess priority setting by academic library administrators and the needs of patrons of digital collections of a public university library in Ghana. Design/methodology/approach – Analysis of official university documents and interviews with digital library patrons at the University of Cape Coast (UCC) in Ghana were carried out between September, 2011 and January, 2012. Five research questions were asked: what are the current conditions of the UCC digital library project, the user communities and their needs, what are the priorities set by the university administrators and library leaders at the UCC and the state of technological readiness in place and what are needed by the UCCDL. Also, what is the extent of collaboration by interested parties in the UCCDL? Findings – Three general digital library user communities were identified, that is, UCCDL staff‐ this community was composed of experts in both digital library systems and content, characterized as heavy users of the existing systems, as knowledgeable about articulated (formalized) user needs, and able to devote short (usually less than two hours) amounts of time to individual's needs. Next, are scholars and other visitors to the UCCDL – this community was characterized as having high levels of domain expertise and knowledge of library systems. They are also able to devote large but specific amounts of time (days or weeks) to their individual information needs. Visitors/Prospective users‐ this community was characterized as having varied levels of domain expertise and low levels of library systems knowledge. They are able to devote only short periods of time to their information needs or explorations. These user communities are influenced by diverse preferences, experiences, and knowledge structures. Practical implications – Academic libraries are increasingly advocating local user studies as a way to provide the digital library services that are relevant to the culture and user population of the academic institution. Replicating digital library user studies at the local level can provide information for improving existing services or developing new ones. Originality/value – In African public universities, there is little earlier research on digital library user needs assessments or DL priority‐setting by academic library administrators.